An Analysis of English for Tourism, Digital Literacy, and Business Success to A Tourist Destination Promotion - Abdul Kadir Ritonga (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The research aims to explore an analysis of English for tourism, digital literacy, business success to promote tourism destinations. The study employed aquantitave research method using cross-sectional. The sample in this study was carried out by non-probability sampling, the accidental sampling technique. Data is collected byusing interviews and observations to collect data from 30 respondents comprising of local tourism stakeholders, including tourism business owners, village officials, and community members in Silalahi 1 village, Dairi regency. The findings indicate thatthe results of the F test show that the value of Fcount is 82.009, so that Fcount> Ftable (82.009> 2.99) and the sig. 0.000 < 0.05. So it can be concluded that english for tourism (X1), digital literacy (X2), and business success (X3) simultaneously have a positive and significant effect on thetourist destinationpromotion (Y). This research contributes to the tourism industry by highlighting the importance of English for tourism, digitalliteracy, and business success as essential tools for promoting tourism destinations in remote areas. It is recommended that tourism stakeholders in the village should invest in digital literacy training, the use of English for tourism literacy, and business success to enhance tourism promotion efforts. Keywords: English for Tourism, Digital Literacy, Promote Tourism Destinations.